2009
DOI: 10.1142/s0218196709005251
|View full text |Cite
|
Sign up to set email alerts
|

Fregean Varieties

Abstract: A class [Formula: see text] of algebras with a distinguished constant term 0 is called Fregean if congruences of algebras in [Formula: see text] are uniquely determined by their 0–cosets and ΘA (0,a) = ΘA (0,b) implies a = b for all [Formula: see text]. The structure of Fregean varieties is investigated. In particular it is shown that every congruence permutable Fregean variety consists of algebras that are expansions of equivalential algebras, i.e. algebras that form an algebraization of the purely equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…This allows us to apply modular commutator theory as described in [2]. In particular, in [6] we have shown that Fregean varieties satisfy the condition (SC1) introduced and discussed in [5]: Proposition 2.1. [6, Theorem 2.3] In a subdirectly irreducible algebra A from a Fregean variety, the centralizer (0 : μ) does not exceed the monolith μ of A.…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations
“…This allows us to apply modular commutator theory as described in [2]. In particular, in [6] we have shown that Fregean varieties satisfy the condition (SC1) introduced and discussed in [5]: Proposition 2.1. [6, Theorem 2.3] In a subdirectly irreducible algebra A from a Fregean variety, the centralizer (0 : μ) does not exceed the monolith μ of A.…”
Section: Preliminariesmentioning
confidence: 99%
“…It is easy to show that the term 0 := xx is constant and that, with 0 being distinguished, the variety E is congruence permutable and Fregean, where (xyz)(xzzx) serves as the Mal'cev term. In fact, the equivalential algebras form a paradigm of congruence permutable Fregean varieties, as the following result, taken from [6], shows. Theorem 1.1.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The author is grateful to prof. K. Słomczyńska for discussing some points related to congruence orderability of the variety of semi-Heyting algebras described in [34] and providing a copy of the paper [22], and to the anonymous referee for various suggestions-in particular, for the improved present version of Theorem 21 and the suggestion to gather in a separate subsection facts concerning relations between known subvarieties of EWR ∧ .…”
mentioning
confidence: 99%